2017
DOI: 10.1016/j.jfluidstructs.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aeration and compressibility on slamming loads during cone water entry

Abstract: International audienceThe problem of the impact between a rigid body and a gas-liquid mixture is relevant to various engineering applications, including the design of breakwaters and LNG containers. In the present study, the particular problem of the impact of a rigid cone upon the surface of an aerated liquid is investigated. Numerical simulations of water entry of cones with different deadrise angles (7° and 15°) were performed using an explicit finite element method. The air-water mixture is modelled as a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…2019; Güzel & Korkmaz 2020), but also by modifying the near-surface region via, for example, aeration (Elhimer et al. 2017) or liquid jet-induced acceleration (Speirs et al. 2019 a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019; Güzel & Korkmaz 2020), but also by modifying the near-surface region via, for example, aeration (Elhimer et al. 2017) or liquid jet-induced acceleration (Speirs et al. 2019 a ).…”
Section: Introductionmentioning
confidence: 99%
“…(Kornhauser 1964;May 1975;Seddon & Moatamedi 2006;Guillet et al 2020). Previous studies have shown that impact forces can be reduced not only through object geometry (McGehee, Hathaway & Vaughan 1959;Thompson 1965;Li & Sigimura 1967;May 1970;Qi et al 2016;Sharker et al 2019;Güzel & Korkmaz 2020), but also by modifying the near-surface region via, for example, aeration (Elhimer et al 2017) or liquid jet-induced acceleration (Speirs et al 2019a). An interesting extension to the idea of free surface modification is to launch a precursory object to agitate the free surface before entry.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are shown in the work of Bredmose et al 16 who also developed a numerical model to simulate this violent flow and capture the shock wave after impact. Moreover, the impact load of a plate and a cone into pure and aerated water is studied respectively by Ma et al 14 and Elhimer et al 17 The necessity of taking the compressibility into account is proved by their work. Despite the influence of aeration effect on the maximum impact load is confirmed, there are still some issues to be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing this peak impact force is of significant interest because it presents structural failure risk to impinging bodies like aircraft landing on water, water landing spacecraft, underwater missiles, divers, base jumpers, etc., (Kornhauser 1964;May 1975;Seddon & Moatamedi 2006;Guillet et al 2020). Previous studies have shown that impact forces can be reduced not only through object geometry (McGehee et al 1959;Thompson 1965;Li & Sigimura 1967;May 1970;Qi et al 2016;Sharker et al 2019;Güzel & Korkmaz 2020), but also by modifying the near-surface region via, for example, aeration (Elhimer et al 2017) or liquid jet-induced acceleration (Speirs et al 2019a). An interesting extension to the idea of free surface modification is to launch a precursory object to agitate the free surface before entry.…”
Section: Introductionmentioning
confidence: 99%